Reinforcing the use of the firms sole needs-based selling tool, the financial needs analysis (FNA) form - Cantago, Jennie Lou G. (Animo Repository, 2014)
This action research is aimed at addressing the pressing problem on the Financial Needs Analysis (FNA) form, which is a standardized diagnostic tool and a mandatory requirement to be submitted with every application since 2012. Since the mandatory submission was a major change for the agency force, Sun Life of Canada (Phils.), Inc. or SLOCPI has been experiencing a high waiver rate for the past two years a clear manifestation of the resistance of the agency force to fully utilize the FNA form. The objectives therefore of the first cycle of this action research project are to reduce the FNA waiver rate by 10%, raise the level of competency of the agency force from Conscious Incompetence to Conscious Competence, and gradually shift 2% of the total agency population from their old ways to the needs-based selling practice by December 2014. To pin down where the resistance is coming from, quantitative (FNA reports and paper survey) and qualitative (brainstorming and informal discussions) methods were administered to five sources particularly FNA report, FMU team, field managers, Sales Training team, and end-users. The results revealed that the underlying causes of the resistance are the reluctance to let go of old ways and lack of competence in FNA execution. The action and reflection cycles, together with the four stages of learning model and Kotter and Schlesingers change management strategies, were then used to diagnose the situation and establish interventions. The actions taken were skewed towards planting awareness and raising the level of competency instead of imposing sanctions. The specific strategies employed to address the two reasons for resistance and in turn alleviate the high waiver rate were education and persuasion, negotiation and agreement, facilitation and support, and manipulation and cooption. To complete the first cycle and evaluate the effectiveness of the project, the FNA forms submitted in October 2014 were reviewed.